Rekonstruksi Sejarah Lokal Perang Panta - Yusra Dewi; Agus Salim (Proceeding International Conference on Malay Identity, 2022)
Abstract: Historical reconstruction must be done because history is not necessarily known to many people. With the reconstruction process, it is hoped that history can serve as an educational, inspirational, instructive, and recreational function for the readers. Therefore, the purpose of this study is to reconstruct the local history of the "Panta War" into reading material that can be used as learning material for Indonesian and History so that educational, inspirational, instructive, and recreational functions can be achieved. The method used to reconstruct this local history is a heuristic method combined with a historical and sociological approach. The research results on the reconstruction of the local history of “War Panta” in the form of a draft book are ready and in the process of printing books with ISBN. According to the validator of reading skills, the results of this reconstruction are suitable for use as reading material. Keywords: reconstruction, historical, Panta War